STUDI ALTERASI DAN MINERALISASI MENGGUNAKAN INTEGRATED MINERAL ANALYZER PADA AREA DEEP GRASBERG, DISTRIK ERTSBERG, PAPUA - Rahmadani, Arsy
The Grasberg Porphyry Cu-Au deposit is one of the largest copper and gold porphyry-type ore deposits discovered on Earth. These Cu-Au systems are associated with K-rich dioritic intrusions, the Grasberg Igneous Complex, which were emplaced into a sedimentary sequence of Tertiary carbonate and Jurassic-Cretaceous siliciclastic rocks. The research area is administratively located in Ertsberg District, Tembagapura Sub-District, Mimika Regency, Papua, at coordinate 734000 E ? 735200 E dan 9550400 N ? 9551600 N. Grasberg Block Cave is an underground mining area which is located exactly under the open mining Grasberg at an elevation of 3300-2600 m and included to the contract area of The Freeport Indonesia Company. This study focuses on the characteristics of the deposit, especially the change of mineralogy, alteration and mineralization zone, and mineralization paragenesis. Eighteen samples from drill core GRD 37-06 and GRD 36-04 are analyzed using Integrated Mineral Analyzer platform which integrates scanning electron microscopy—energy dispersive spectroscopy (SEM-EDS) with mineral identification software. Besides using Integrated Mineral Analyzer, the samples are also analyzed by polarizing and reflecting microscope. Several minerals such as plagioclase, biotite, anhydrite, and chalcopyrite tend to be abundant in the core of the Grasberg Igneous Complex. While, the other minerals such as muscovite and covellite tend to be abundant in the outer part. There are three alteration zones in the research area, they are Quartz – K-feldspar – Biotit ± Anhydrite Zone (?Potassic Zone), Quartz – Muscovite – Pyrite Zone (?Phyllic Zone), and Quartz – K-feldspar – Musovite Zone. Mineralization paragenesis of the research area can be divided into two phases. The initial phase of mineralization is characterized by the presence of pyrite, chalcopyrite, and magnetite. The next phase is supergene enrichment and characterized by the presence of pyrite and covellite.